2002
DOI: 10.1124/jpet.301.3.1157
|View full text |Cite
|
Sign up to set email alerts
|

Ranitidine Reduces Ischemia/Reperfusion-Induced Liver Injury in Rats by Inhibiting Neutrophil Activation

Abstract: We previously reported that ranitidine, an H 2 receptor antagonist, inhibited neutrophil activation in vitro and in vivo, contributing to reduce stress-induced gastric mucosal injury in rats. In this study, we examined whether ranitidine would reduce ischemia/reperfusion-induced liver injury, in which activated neutrophils are critically involved, in rats. We also examined the effect of famotidine, another H 2 receptor antagonist, on leukocyte activation in vitro and after ischemia/reperfusion-induced liver in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 43 publications
2
37
0
Order By: Relevance
“…Interestingly, RAN attenuates liver injury after ischemia-reperfusion, probably by inhibiting release of cytotoxic factors by PMNs (Okajima et al, 2002). Previous studies demonstrated that RAN was nontoxic to hepatocytes even at high (e.g., 5 mM) concentrations (Zimmerman et al, 1986), and our results confirmed these findings (Fig.…”
Section: Inflammation and Ranitidine Idiosyncrasy 13supporting
confidence: 82%
“…Interestingly, RAN attenuates liver injury after ischemia-reperfusion, probably by inhibiting release of cytotoxic factors by PMNs (Okajima et al, 2002). Previous studies demonstrated that RAN was nontoxic to hepatocytes even at high (e.g., 5 mM) concentrations (Zimmerman et al, 1986), and our results confirmed these findings (Fig.…”
Section: Inflammation and Ranitidine Idiosyncrasy 13supporting
confidence: 82%
“…Accordingly, PMNs require a secondary signal provided by RAN treatment to be activated and cause damage. RAN itself does not activate PMNs directly; in fact, it inhibits PMN activation both in vitro and in vivo (Okajima et al, 2000(Okajima et al, , 2002. This suggests that RAN acts indirectly through other inflammatory mediators produced during LPS exposure.…”
Section: Involvement Of Hemostasis Neutrophils and Tumor Necrosis Fmentioning
confidence: 90%
“…The possibility that ranitidine might act through other receptors besides HA-H 2 could not be excluded. 21 It is also possible that HA released from microglia or astroglia 22 during OGD could directly potentiate glutamate receptor-mediated cell death by interacting with the polyamine-binding site of the NMDA receptor complex. 8 Ranitidine could then be able to antagonize HA interaction with NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%